FLAVONOID COMPOSITION OF THE MEDICINAL PLANT GOLDEN ROOT (Scientific journal of the Fergana State University, 2023)
This article is devoted to the experimental study of flavonoid composition of the medicinal plant "Golden Root", found in the regions of Uzbekistan, with the method of high-performance liquid chromatography. Golden root is aimed at scientific substantiation that in diseases of the nervous system, in particular, when used for the prevention and treatment of memory impairment (encephalopathy), the plant gives a good effect, since it is rich in biologically active flavonoids.